Do the Olympic Games promote dietary health for spectators? An interdisciplinary study of health promotion through sport. Issue 4 (8th August 2019) - Piggin, Joe; Souza, Doralice Lange de; Furtado, Sabrina; Milanez, Matheus; Cunha, George; Louzada, Bruno Henrique; Graeff, Billy; Tlili, Haifa
ABSTRACT: Research question: Debates about dietary health promotion at sports events are becoming more prominent and are making food and drink sport sponsorship arrangements increasingly problematic. This study uses choice architecture as a guiding framework to examine how ideas about 'healthy choices' for customer food and drink were operationalised at the Rio 2016 Olympic and Paralympic Games in Brazil. Research methods: An interdisciplinary perspective was applied, whereby considerations of public health, marketing, psychology, policy studies, nutrition and event management informed the research. A multi-method approach was utilised, which included policy analysis, menu analysis, event process analysis, and interviews with spectators. The data were compared and contrasted to see how ideas about health manifested in policy and practice, culminating in the Rio 2016 event. Results and findings: While 'healthy choice' claims featured prominently in Rio 2016 policy, the practical reality consisted of spaces with both a very low amount of choice for Olympic spectators, and a large amount of high- and ultra-processed food. Rio 2016 organisers shaped the choice architecture so that the food and drink being sold and consumed met neither the spectators' nor Brazilian policy definitions of health. Implications: The results show a need for organisers of sport events to question and challenge popular claims of health promotion. Recommendations for governments and sport organisations include the need to alter the accepted production practices of sport mega events, especially since the events are often in receipt of public money and involve unfulfilled claims about health promotion.